Comparison of physical activity and body composition in a cohort of children born extremely preterm or with extremely low birth weight to matched term-born controls: a follow-up study - Maria Vollsæter; Geir Egil Eide; Thomas Halvorsen; Mette Engan; Knut Øymar; Trond Markestad; Petur Juliusson; Hege Clemm (BMJ Publishing Group, 2019)
Objectives To compare physical activity and body composition in a cohort of children born extremely preterm/extremely low birth weight (EP/ELBW) with term-born (TB) controls.Methods A regional cohort of children born during 1999-2000 at gestational age <28 weeks or with birth weight <1000 g and their individually matched TB controls were examined in 2010-2011. Information on physical activity was obtained from parental questionnaires, and body composition was determined by anthropometry and dual X-ray absorptiometry.Results Fifty-seven EP/ELBW and 57 TB controls were included at a mean age of 11.6 years. Compared with the TB children, the EP/ELBW-born children exercised less often (22% vs 44% exercised more than 3 days per week), had lower physical endurance and poorer proficiency in sports and play and were less vigorous during exercise (p<0.05). They also had lower values (mean; 95 % CI) for muscle mass (0.9; 0.3-1.5 kg), total bone mineral density z-score (0.30; 0.13-0.52 units) and fat mass ratio (0.14; 0.06-0.21 units). The association between physical activity and bone mineral and skeletal muscle mass accrual was significantly weaker for the EP/ELBW-born than the TB children.Conclusions The EP/ELBW-born children were less physically active, had signs of an unfavourable body composition with less muscle mass and lower bone mineral density than the TB controls. The association between physical activity and the measures of body composition was weaker in the group of EP/ELBW-born children.